2015
DOI: 10.1111/pcn.12277
|View full text |Cite
|
Sign up to set email alerts
|

Possible relation between olfaction and anxiety in healthy subjects

Abstract: Aims: While olfaction is a sense closely associated with the limbic system and emotions, the relation between emotional status and olfactory functioning has not been well documented. This study aimed to examine the possible effect of anxiety on olfaction in healthy subjects. Methods:We investigated the effect of state and trait anxiety on the detection and recognition thresholds for five different odors in 124 healthy subjects (62 men and 62 women, mean age = 27.2 years) using a T&T olfactometer.Results: While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Depressed patients are more likely to have olfactory dysfunction, and anosmic patients are more likely to exhibit depressive symptoms (Pause et al 2001;Croy et al 2012Croy et al , 2014. Though less well-established than the relationship with depression, olfaction and anxiety may be associated (Takahashi et al 2015); anxiety was measured with the NSHAP Anxiety Symptoms Measure (NASM), derived from the Hospital Anxiety and Depression Scale's Anxiety Subscale (La Buissonnière-Ariza et al 2013; Payne et al 2014). Finally, selfreported physical and mental health were included as potential confounders in order to account for possible individual bias towards optimistic or pessimistic self-report of all health variables.…”
Section: Potential Confounding Variablesmentioning
confidence: 99%
“…Depressed patients are more likely to have olfactory dysfunction, and anosmic patients are more likely to exhibit depressive symptoms (Pause et al 2001;Croy et al 2012Croy et al , 2014. Though less well-established than the relationship with depression, olfaction and anxiety may be associated (Takahashi et al 2015); anxiety was measured with the NSHAP Anxiety Symptoms Measure (NASM), derived from the Hospital Anxiety and Depression Scale's Anxiety Subscale (La Buissonnière-Ariza et al 2013; Payne et al 2014). Finally, selfreported physical and mental health were included as potential confounders in order to account for possible individual bias towards optimistic or pessimistic self-report of all health variables.…”
Section: Potential Confounding Variablesmentioning
confidence: 99%
“…A growing literature indicates structural and functional changes of the olfactory system with fear and threat ( Ahs et al, 2013 , Jones et al, 2008 , Kass et al, 2013 ), as well as olfactory differences with anxiety ( La Buissonniere-Ariza et al, 2013 , Takahashi et al, 2015 ) and fear-related disorders, including posttraumatic stress disorder (PTSD) ( Berlin et al, 2017 , Buron et al, 2015 , Cortese et al, 2015b , Dileo et al, 2008 , Vasterling et al, 2000 ). These observations suggest a linkage between the neurobiology of olfactory function and anxiety-fear systems.…”
Section: Introductionmentioning
confidence: 99%
“…Before and after the picture encoding-retrieval memory tasks, participants completed an odor rating task and filled questionnaires regarding their affective state (as assessed with the Positive and Negative Affect Schedule, PANAS; Watson, Clark, & Tellegen, 1988; German version, Janke & Glöckner-Rist, 2014 and anxiety state Spielberger, 1968). Information regarding affective and anxiety states were collected because previous studies have shown that olfactory perception can be modulated by emotional states (Kadohisa, 2013;Krusemark, Novak, Gitelman, & Li, 2013;Takahashi et al, 2015; see Data S1 for the results of mood assessment). The odor rating was done to familiarize all participants with the masked body odor or with the masker odor that was used in the subsequent stages of the study (compare Reichert et al, 2017) and to make sure that the masking procedure worked.…”
Section: Odor Ratings and Mood Assessmentmentioning
confidence: 99%